Analisis Pengaruh Green Product Knowledge dan Green Trust Terhadap Green Purchase Intention Customer Produk Eiger Kota Surakarta - Windi Shilvia Puspitasari; Umi Hanifah; Agus Suyatno (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of green product knowledge and green trust on green purchase intention among Eiger product consumers in Surakarta City. The background of this study is the increasing volume of waste from the fashion industry which has a negative impact on the environment. This encourages companies, including Eiger, to start implementing sustainable business strategies to increase consumer interest in environmentally friendly products. One of these strategies is by strengthening education about green products (green product knowledge) and building consumer trust in the company's environmental commitment (green trust), which is believed to influence green product purchase intention. This study uses a quantitative approach with 100 respondents selected using a purposive sampling technique. The respondent criteria are Eiger consumers who live in Surakarta City and have purchased Eiger products. Data collection was carried out by distributing questionnaires, then analyzed using IBM SPSS Statistics software version 25. The data analysis procedure includes instrument validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, and hypothesis testing. The results of the study indicate that both green product knowledge and green trust have a positive and significant effect on green purchase intention. This indicates that the higher consumers' knowledge of environmentally friendly products and the greater their trust in a company's sustainability commitment, the greater their tendency to purchase green products. This finding provides strategic implications for companies like Eiger to continue improving consumer education and transparency regarding sustainability practices to strengthen customer loyalty and purchase intention for green products.